Analisis Tindak Tutur Dalam Wacana Parenting Podcast Mom’s Cornet Nikita Willy. - NURFADILLAH; Zulfiani ramaadhani azis; Abdul Halik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to analyze the forms and intent of expressive, assertive,directive, and commissive speech acts in mom's cornet Nikita Willy's podcast. This type ofresearch is descriptive research using a qualitative approach. The data from this studycame from the Mom's Cornet podcast hosted by Nikita Willy with the title